1975
DOI: 10.1111/j.1755-3768.1975.tb01777.x
|View full text |Cite
|
Sign up to set email alerts
|

Histology of the Iris in Geese and Ducks Photosensitized by Ingestion of Ammi Majus Seeds

Abstract: Geese and ducks were photosensitized by the ingestion of Ammi majus seeds, and exposure to sunlight. Mydriasis was a characteristic clinical feature of this syndrome in both species. Histologically the iris of the affected birds showed vacuolisation and varying degrees of atrophy of the muscle of the sphincter pupillae. The effect of pilocarpine and physostigmine on the normal and mydriatic eyes was studied. The possible mode of action of photosensitization and the significance of these findings in the light o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Photosensitization in ducklings has shown vacuolization of retinal ganglion cells, pigmentary retinopathy, and congestion of choroidal vessels. [ 6 ] It is plausible that in our patient, methoxsalen being a photosensitizing drug may interact with clofazimine, making the macula more sensitive to light-induced damage as the drug is reported to be very safe in the usual doses in nonimmunocompromised adults. [ 7 ] The appearance of central scotoma before visible changes in the fundus suggests that the initial site of damage is in the outer segment of the photoreceptors, which is then followed by degeneration of the retinal pigment epithelium (RPE) and choriocapillaris.…”
Section: Discussionmentioning
confidence: 99%
“…Photosensitization in ducklings has shown vacuolization of retinal ganglion cells, pigmentary retinopathy, and congestion of choroidal vessels. [ 6 ] It is plausible that in our patient, methoxsalen being a photosensitizing drug may interact with clofazimine, making the macula more sensitive to light-induced damage as the drug is reported to be very safe in the usual doses in nonimmunocompromised adults. [ 7 ] The appearance of central scotoma before visible changes in the fundus suggests that the initial site of damage is in the outer segment of the photoreceptors, which is then followed by degeneration of the retinal pigment epithelium (RPE) and choriocapillaris.…”
Section: Discussionmentioning
confidence: 99%
“…Thus 8-MOP has an affinity for melanin and its precursors (Ebling & Rook 1972), and it has also been shown to increase tyrosinase activity in tissues (Chakraborty et al 1976). Barishak (1975) has fed geese and ducks with Ammi Majus seed (which contains 5-and 8-MOP), and this produced vacuoles in the sphincter of the pupil, and, in chronic cases, uveal atrophy and ectropy. Egyed et al (1975) have demonstrated a pigmentary retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…to experimental animals have been made by nu inerous investigators (Griffin 1959;Cloud et al 19(;0, 1961;Freeman 1966;Freeman & Troll 19fi9; Shlosberg et a]. 1974; Egyed et al , 1975Barishak et al 1975Barishak et al , 1976Singer et al 1976;Mikuni et al 1977;Witzel et al 1978;Jose & Yielding 1978;Clew 1979;Koch et al 1979;Jose et al 1982;Boutrous et al 1984). In contrast, PI' VA, administered chronically to rabbits at doses providing tolerable cutaneous effects, has also bec,n reported to cause no ocular damage (Parrish et .rl.…”
mentioning
confidence: 99%